"There is no free here, you have to pay": actual and perceived costs as barriers to intermittent preventive treatment of malaria in pregnancy in Mali. (December 2016) - Klein, Meredith; Harvey, Steven; Diarra, Hawa; Hurley, Emily; Rao, Namratha; Diop, Samba; Doumbia, Seydou
Abstract Background "There is no free here, " the words of a Malian husband, illustrate how perceptions of cost can deter uptake of intermittent preventive treatment of malaria in pregnancy (IPTp). The Malian Ministry of Health (MOH) recommends a minimum of three doses of IPTp at monthly intervals. However, despite a national policy that IPTp be provided free of charge, only 35 % of pregnant women receive at least one dose and less than 20 % receive two or more doses. Methods This study explored perceptions and experiences of IPTp cost in Mali and their impact on uptake, using qualitative interviews and focus groups with pregnant women, husbands and mothers-in-law. Study team members also interviewed and observed health workers at four health centres, two in Sikasso Region and two in Koulikoro. Results Despite national-level policies, actual IPTp costs varied widely at study sites—between facilities, and visits. Pregnant women may pay for IPTp, receive it free, or both at different times. Health centres often charge a lump sum for antenatal care (ANC) visits that includes both free and fee-based drugs and services. This makes it difficult for women and families to distinguish between free services and those requiring payment. As a result, some forego free care that, because it is bundled with other fee-based services and medications, appears not to be free. Varying costs also complicate household budgeting for health care, particularly as women often rely on their husbands for money. Finally, while health facilities operating under the cost-recovery model strive to provide free IPTp, their own financial constraints often make this impossible. Conclusions Both actual and perceived costs are currently barriers to IPTp uptake. Given the confusion around cost of services in the two study regions, more detailed national-level studies of both perceived and actual costs could help inform policy and programme decisions promoting IPTp. These studies should evaluate both quantitatively and qualitatively the cost information provided to and understood by pregnant women and their families. Meanwhile, unbundling free and fee-based services, making clear that IPTp is free, and ensuring that it is provided at no cost could help increase uptake. Free community-based distribution might be another route to increased uptake and adherence.